Предмет: Алгебра,
автор: tqjsychfkeyaxeudn
Решите пжжж дам 30 баллов
Приложения:
Ответы
Автор ответа:
0
Объяснение:
10√(х-3)^2=8
10х-30=8
10х=8+30
х=38/10=3,8
(х+1)√3=х+3
√(3(х+1)^2=х+3
3(х^2 +2х+1)=(х+3)^2
3х^2 +6х+3=х^2 +6х+9
3х^2 +6х-х^2 -6х=9-3
2х^2=6
х^2=6/2
х=√3
(2-x√6)√2=2·(x-√6)
2-x√6=√2 ·(x-√6)
2-x√6=x√2 -√(2·6)
x√6 +x√2=2+√12
x(√6 +√2)=2+√12
x²(√6 +√2)²=(2+√12)²
x²(6+2√12 +2)=4+4√12 +12
x²(8+2√12)=16+4√12
2x²(4+√12)=4(4+√12)
x²=2
x=√2
(x√5 -2)√10=5x-2√5
(x√5 -2)√10=√5(x-2√5)
(x√5 -2)√2=x-2√5
(x√5 -2)²·√2²=(x-2√5)²
2(5x²-4x√5 +4)=x²-4x√5 +20
10x²-4x√5 -x²+4x√5=20-4
9x²=16
x²=16/9
x=4/3=1 1/3
Похожие вопросы
Предмет: Физика,
автор: lidiagus1971
Предмет: Алгебра,
автор: Vovathexs
Предмет: Музыка,
автор: Sashakyzminova5252
Предмет: Математика,
автор: tori39